Perioperative utility of amisulpride and dopamine receptor antagonist antiemetics-a narrative review - Elias, Murad; Gombert, Alexa; Siddiqui, Sulaimaan; Yu, Sun; Jin, Zhaosheng; Bergese, Sergio (Frontiers in Pharmacology, 2023)
Despite advances in antiemetics and protocolized postoperative nausea vomiting (PONV) management, it remains one of the most common postoperative adverse events. In patients who developed PONV despite antiemetic prophylaxis, giving a rescue treatment from the same class of medication is known to be of limited efficacy. Given the widespread use of 5-HT3 antagonists as PONV prophylaxis, another class of effective intravenous rescue antiemetic is in dire need, especially when prophylaxis fails, and rescue medication is utilized. Dopamine antagonists were widely used for the treatment of PONV but have fallen out of favor due to some of their side effect profiles. Amisulpride was first designed as an antipsychotic medication but was found to have antiemetic properties. Here we will review the historical perspective on the use of dopamine receptor antagonist antiemetics, as well as the evidence on the efficacy and safety of amisulpride.Postoperative nausea and vomiting (PONV) is one of the most common adverse events to occur postoperatively, occurring in up to 30% of patients. In high-risk patients, this number can be as high as 70% (1). It is second only to postoperative pain in terms of the most common complaints by patients following surgery. Furthermore, it is a significant source of distress and patient dissatisfaction (2). With a growing trend towards ambulatory and same day surgeries, it is also a major source of delaying discharges from post-anesthesia care units (PACU) (3). A single episode of PONV can delay discharge from the PACU by about 25 minutes (4). This can sometimes lead to unanticipated hospital admission and ultimately lead to an overall increase in healthcare costs (5). Being able to identify high-risk patients and treat them with the appropriate prophylaxis can greatly improve patient care and satisfaction.